The Effectiveness of the Pacta Sunt Servanda Principle in Providing Legal Protection for Construction Service Sub-Providers - Iswandi, Wahyu; Subekti; Paramita , Vallencia N. (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2026)
The involvement of subcontractors in construction contracts is a practical necessity for carrying out work that requires specialized expertise. However, the position of subcontractors in contractual relationships still faces problems due to unequal bargaining positions and potential imbalances in contractual clauses. This study aims to analyze legal protection for subcontractors under the principle of pacta sunt servanda and to examine the role of the principle of contractual justice in maintaining the balance of the parties' rights and obligations. The results of the study indicate that the principle of pacta sunt servanda provides certainty regarding the validity of the contract, but has not fully guaranteed protection for subcontractors in an unbalanced contractual relationship. Positive legal regulations still leave room for ambiguity regarding the position and fulfillment of subcontractor rights. Strengthening the principles of contractual fairness, good faith, and proportionality is necessary to create fairer, more balanced contractual relationships and provide legal certainty for subcontractors in construction work contracts.